2021
DOI: 10.1590/1678-4324-2021200748
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Antioxidant Effects of the Microalga Pediastrum boryanum in Carrageenan-Induced Rat Paw Edema

Abstract: The potential use of microalgae in health has been the aim of different studies in the last years. This study investigated anti-inflammatory and antioxidant properties of three different extracts of green microalga Pediastrum boryanum in an acute inflammation model in rats. Rats were treated intraperitoneally with lyophilized biomass, the phenolic compounds and the extracellular extracts of P. boryanum before the induction of paw edema by the intraplantar injection of carrageenan. The edema and the levels of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Turning to the anti-inflammatory activity of Hypnea musciformis, our results indicated a concentration-dependent protective effect, aligning with a decrease in hemolysis as the extract concentration increased from 100 to 200 µg/ml. This suggests that the aqueous extract may stabilize the RBC membrane, thereby offering protection against hemolysis (22). A similar protective effect was reported by Silva M, et al, in 2022, wherein an ethanolic crude extract of P.chaba mirrored the efficacy of acetylsalicylic acid at 500 µg/ml (22).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Turning to the anti-inflammatory activity of Hypnea musciformis, our results indicated a concentration-dependent protective effect, aligning with a decrease in hemolysis as the extract concentration increased from 100 to 200 µg/ml. This suggests that the aqueous extract may stabilize the RBC membrane, thereby offering protection against hemolysis (22). A similar protective effect was reported by Silva M, et al, in 2022, wherein an ethanolic crude extract of P.chaba mirrored the efficacy of acetylsalicylic acid at 500 µg/ml (22).…”
Section: Discussionsupporting
confidence: 59%
“…This suggests that the aqueous extract may stabilize the RBC membrane, thereby offering protection against hemolysis (22). A similar protective effect was reported by Silva M, et al, in 2022, wherein an ethanolic crude extract of P.chaba mirrored the efficacy of acetylsalicylic acid at 500 µg/ml (22).…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, the dietary addition of 0.5% of red algal extract ( Laurencia caspica ) to the Nile tilapia showed a significantly increased in lysozyme and IgM activities after 50 d [ 41 ]. It has been suggested that P. boryanum supplementation elicits B lymphocytes owing to its polysaccharide content, thereby augmenting both innate and adaptive immune responses [ 13 ]. Additionally, arachidonic acid, a precursor of biologically active prostaglandins and leukotrienes, promotes leukocyte chemotaxis, reactive oxygen species formation, and other pro-inflammatory effects [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies concerning P. boryanum in other animal species revealed same effects as well, Ahmed et al [ 40 ], showed no statistical changes in liver enzyme levels (ALT and AST) or plasma albumin in New Zealand white rabbits fed Pediastrum spp. Silva et al [ 13 ] showed that the administration of various P. boryanum extracts did not alter the serum levels of the liver enzymes ALT and AST in rats. Fonseca et al [ 47 ] reported no significant increases in liver ALT and AST enzymes in mice orally administered 300 mg/kg or 2000 mg/kg freeze-dried P. boryanum biomass suspended in carboxymethyl cellulose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation